Unconfined compressive strength and erodibility of gypsum-treated Diliman silt - Quinto, Adan Jacov A.; Ridon, Ian Levy
The main goal of this study is to measure the unconfined compression strength and erodibility of soil mixed with gypsum. There is only a little research done using gypsum as an additive to soil. Gypsum can be more usable to humans in the form of Plaster of Paris. In this research, Plaster of Paris was used as the binding medium. It is mixed with soil and water. Two quantities of gypsum (20% and 30% (by mass)) were used to make specimens. For each gypsum percentage, two moisture contents were considered. Furthermore, each gypsum-water ratio was cured for two curing times (7 days and 14 days). All of these soil samples were tested for their compressive strength using a digital Universal Testing Machine. For erodibility, only the moisture content and curing period that produced the greatest strength were chosen to each gypsum percentage to create specimens. The researchers designed a Constant Head Apparatus to measure the erodibility of untreated and treated soil samples. Treating soil samples with gypsum greatly improved the unconfined compressive strength and erodibility of soil. The unconfined compressive strength of gypsum - treated soil specimen increased with respect to longer curing time period. It was also observed that the unconfined compressive strength of soil samples were highest at the optimum moisture content. When treated soil specimens were compared with the erodibility of untreated soil specimens, significant difference can be observed.